Jurnal Penyuluhan: Tingkat Partisipasi dalam Kegiatan Pendidikan Kecakapan Hidup - Lina Asnamawati, Ninuk Purnaningsih, Soenarmo J. Hatmodjosoewito (PPs ILMU PENYULUHAN PEMBANGUNAN IPB, 2014)
Life skill education is an essential thing that must be owned by people to gain knowledge and practical skill in particular work fields. The success of life skill education was determined by the direct involvement of the society based on the planning, implementation, evaluation, and benefit of the result.